PEMAHAMAN KONSEP MATEMATIKA MENGGUNAKAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING DAN GROUP INVESTIGATION - Sitti Fatimah; Fitriani Nur; Suharti Suharti; Sri Sulasteri; Andi Dian Angriani (Universitas Pekalongan, 2021)
The purpose of this research is to determine whether there are differences in the understanding of the concept of students who learn by applying the model Problem Based Learning with Group Investigation. This research in to the type of quasi-experimental design of non-equivalent pretest-posttest control group. The samples taken were class XI IPA 2 (experimental class I) and class XI IPA 3 (experimental class II). The instrument applied was a learning outcome test containing 5 items. Data analysis was calculated using analysis techniques: descriptive and inferential. The results of the descriptive data obtained mean scores of 44.81 pretest and 76.54 posttest for the experimental class I, while the experimental class II scored 47.54 pretest and 84.14 posttest. From the independent sample test, it was obtained a sign score: 0.000 at a significance level of 5%. This means that H0 is rejected, so it was decided that the level of conceptual understanding for the model is Problem Based Learning different from the level of concept understanding in the model Group Investigation.